Mutational landscape of mucinous ovarian carcinoma and its neoplastic precursors. Issue 1 (December 2015) - Ryland, Georgina; Hunter, Sally; Doyle, Maria; Caramia, Franco; Li, Jason; Rowley, Simone; Christie, Michael; Allan, Prue; Stephens, Andrew; Bowtell, David; Campbell, Ian; Gorringe, Kylie
Abstract Background Mucinous ovarian tumors are an unusual group of rare neoplasms with an apparently clear progression from benign to borderline to carcinoma, yet with a controversial cell of origin in the ovarian surface epithelium. They are thought to be molecularly distinct from other ovarian tumors but there have been no exome-level sequencing studies performed to date. Methods To understand the genetic etiology of mucinous ovarian tumors and assess the presence of novel therapeutic targets or pathways, we undertook exome sequencing of 24 tumors encompassing benign (5), borderline (8) and carcinoma (11) histologies and also assessed a validation cohort of 58 tumors for specific gene regions including exons 4–9 ofTP53 . Results The predominant mutational signature was of C>T transitions in a NpCpG context, indicative of deamination of methyl-cytosines. As well as mutations in known drivers (KRAS, BRAF andCDKN2A ), we identified a high percentage of carcinomas withTP53 mutations (52 %), and recurrent mutations inRNF43, ELF3, GNAS, ERBB3 andKLF5 . Conclusions The diversity of mutational targets suggests multiple routes to tumorigenesis in this heterogeneous group of tumors that is generally distinct from other ovarian subtypes.